2013
DOI: 10.1093/jnci/djt300
|View full text |Cite
|
Sign up to set email alerts
|

Human Gut Microbiome and Risk for Colorectal Cancer

Abstract: We tested the hypothesis that an altered community of gut microbes is associated with risk of colorectal cancer (CRC) in a study of 47 CRC case subjects and 94 control subjects. 16S rRNA genes in fecal bacterial DNA were amplified by universal primers, sequenced by 454 FLX technology, and aligned for taxonomic classification to microbial genomes using the QIIME pipeline. Taxonomic differences were confirmed with quantitative polymerase chain reaction and adjusted for false discovery rate. All statistical tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
644
5
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 805 publications
(700 citation statements)
references
References 26 publications
46
644
5
5
Order By: Relevance
“…As shown in Fig. 3B, Upper, the alpha diversity decreased drastically (50% on average) in all groups after 38 d. This loss of community diversity can be explained by the tumor-induced dysbiosis in the gut bacteria community, consistent with previous findings that some diseases could lead to an imbalanced gut microbiota and decrease the ecological diversity in the gut (21,22). When comparing the alpha diversity between the 38-d samples, we observed no significant difference between the control and ProTreat groups; however, cisplatin and ProPre groups showed significantly higher alpha diversity than both the control and ProTreat (Bonferroni adjusted P value < 0.05, Wilcoxon rank-sum test using 100 bootstrap samples).…”
Section: Probiotics Mediate the Structural And Functional Compositionsupporting
confidence: 89%
“…As shown in Fig. 3B, Upper, the alpha diversity decreased drastically (50% on average) in all groups after 38 d. This loss of community diversity can be explained by the tumor-induced dysbiosis in the gut bacteria community, consistent with previous findings that some diseases could lead to an imbalanced gut microbiota and decrease the ecological diversity in the gut (21,22). When comparing the alpha diversity between the 38-d samples, we observed no significant difference between the control and ProTreat groups; however, cisplatin and ProPre groups showed significantly higher alpha diversity than both the control and ProTreat (Bonferroni adjusted P value < 0.05, Wilcoxon rank-sum test using 100 bootstrap samples).…”
Section: Probiotics Mediate the Structural And Functional Compositionsupporting
confidence: 89%
“…Recent studies have shown that Fusobacterium, especially Fusobacterium nucleatum (Fn), is associated with colorectal cancer. Fn is enriched in both the feces and colonic mucosa of colorectal cancer patients (3,5,8) and plays important roles in colorectal carcinogenesis (9,10). In our recent study, using 16S rRNA sequencing to catalog the microbial communities in human gut mucosa at different stages of colorectal tumorigenesis, Fusobacterium was also found to be enriched in colorectal tumors (11).…”
Section: Introductionmentioning
confidence: 93%
“…These candidates were identified by eliminating confounding effects of colonoscopy using blocked independent Wilcoxon rank-sum tests with colonoscopy as a stratifying factor in our previous metagenome study (12). Fn has also been identified to be enriched in colorectal cancer patients by others (3,5,8), while the other four have not associated with colorectal cancer by other researchers. Primer and probe sequences targeting the nusG gene of Fn (Accession# GMHS-1916) and gene markers identified by our previous metagenome sequencing study, including Bc (ID 370640), Ch (ID 2736705), Ri (ID 181682), and m7 (ID 3246804; ref.…”
Section: Design Of Primers and Probesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this study did not imply a more diverse microbiota is 'preferable' in terms of health, others have certainly implied this through association [60][61][62]. Such conclusions, regardless of the different tools used to acquire the data, should also be treated with caution.…”
Section: Effects Of Diets On the Gut Microbiota In Five Continentsmentioning
confidence: 67%